2015
DOI: 10.1007/s00774-015-0703-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and osteoporosis: a systematic review and meta-analysis

Abstract: were included in the meta-analysis. Four were crosssectional studies and one was a prospective cohort study. Studies were performed in Japan, South Korea, and Taiwan. All except Asaoka et al. [4] included only postmenopausal women. We performed a meta-analysis using a random-effects model. There is no significant association between H. pylori infection and osteoporosis with pooled OR = 1.49 (95 % CI 0.88-2.55, p = 0.14, I 2 = 52 %, P heterogeneity = 0.08).From this result, we demonstrated that H. pylori infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 5 publications
2
34
1
1
Order By: Relevance
“…A systemic review conducted by Upala S et al concluded that the H. pylori infection was positively associated with MetS, higher TG, FPG, BMI, HOMA-IR, systolic blood pressure and lower HDL-C, most of which were compatible to the results in our study [35]. However, previous reports showed some inconsistencies regarding different components of MetS affected by H. pylori infection.…”
Section: Discussionsupporting
confidence: 91%
“…A systemic review conducted by Upala S et al concluded that the H. pylori infection was positively associated with MetS, higher TG, FPG, BMI, HOMA-IR, systolic blood pressure and lower HDL-C, most of which were compatible to the results in our study [35]. However, previous reports showed some inconsistencies regarding different components of MetS affected by H. pylori infection.…”
Section: Discussionsupporting
confidence: 91%
“…These results showed a pathogenic linkage between HPI and diabetes [74] . There were significant differences of fasting blood glucose, high-density lipoprotein cholesterol between HPI patients and healthy controls [75] . Hsieh et al reported that long-term HPI was significantly associated with increased levels of HbA1c and decreased insulin secretion in Chinese population [76] .…”
Section: Diabetes Mellitusmentioning
confidence: 84%
“…pylori infection is reported to be associated with insulin resistance, diabetes mellitus and metabolic syndrome [74][75][76] . Compared to non-diabetics with HPI, the levels of oxidative DNA damage (8-OHdG) in type 2 diabetes mellitus could be much higher (p = 0.001).…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Recently, a meta-analysis using 5 studies [15,18,20,21,44] from Asian countries demonstrated that H. pylori infection does not seem to be an important factor related to osteopenia [45]. However, some previous studies showed a relationship between H. pylori infection and osteoporosis [16,17,18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%